Exploring the potential role of four Rhizophagus irregularis nuclear effectors: opportunities and technical limitations - Aparicio Chacón, María Victoria; Hernández Luelmo, Sofía; Devlieghere, Viktor; Robichez, Louis; Leroy, Toon; Stuer, Naomi; De Keyser, Annick; Ceulemans, Evi; Goossens, Alain; Goormachtig, Sofie; Van Dingenen, Judith (Frontiers in Plant Science, 2024)
Arbuscular mycorrhizal fungi (AMF) are obligate symbionts that interact with the roots of most land plants. The genome of the AMF model species Rhizophagus irregularis contains hundreds of predicted small effector proteins that are secreted extracellularly but also into the plant cells to suppress plant immunity and modify plant physiology to establish a niche for growth. Here, we investigated the role of four nuclear-localized putative effectors, i.e., GLOIN707, GLOIN781, GLOIN261, and RiSP749, in mycorrhization and plant growth. We initially intended to execute the functional studies in Solanum lycopersicum, a host plant of economic interest not previously used for AMF effector biology, but extended our studies to the model host Medicago truncatula as well as the non-host Arabidopsis thaliana because of the technical advantages of working with these models. To get insight into effector function during AM symbiosis, we used ectopic overexpression in the host Medicago truncatula, whereas the stable transgenic lines of the non-host Arabidopsis thaliana were used to investigate their conservatory role in growth. Furthermore, for three effectors, the implementation of reverse genetic tools, yeast two-hybrid screening and whole-genome transcriptome analysis revealed potential host plant nuclear targets and downstream triggered transcriptional responses. We identified and validated a host protein interactor participating in mycorrhization in the host .SolanumS. lycopersicum and demonstrated by transcriptomics the effector's possible involvement in different molecular processes, i.e., the regulation of DNA replication, methylglyoxal detoxification, and RNA splicing. We conclude that R. irregularis nuclearlocalized effector proteins may act on different pathways to modulate symbiosis and plant physiology and discuss the pros and cons of the tools used.